Pengaruh intellectual capital terhadap financial performance dengan corporate reputation sebagai variabel moderasi - Putri Purnama Sari; Rosyeni Rasyid (Jurnal Kajian Manajemen dan Wirausaha, 2020)
This study aims to analyze whether there is an effect of intellectual capital on financial performance as moderated by the company's reputation. The financial performance is seen from the financial ratios, namely the ratio of profitability (return on assets).  This type of research is classified into comparative research. The population in this study were 45 banks listed on the Indonesian stock exchange in 2014-2018. Sampling in this study using purposive sampling method in order to obtain a sample of 36 banks with a total sample of 180 samples. The type of data used is secondary data obtained from the official website of the Indonesian stock exchange www.idx.id  and published financial reports on the websites of each bank sample. Based on the results of the regression test with a significant level of 0.1; The results obtained indicate (1) there is a significant effect of intellectual capital on financial performance. (2) company reputation moderates the relationship between intellectual capital and financial performance. Keywords: Intellectual capital, financial performance, company reputation